Maturation of human iPS cell-derived dopamine neuron precursors in alginate–Ca2+ hydrogel - Komatsu, Mitsue; Konagaya, Shuhei; Egawa, Edgar Y.; Iwata, Hiroo (Biochimica et biophysica acta. General subjects, 2015)
Pluripotent stem cells (embryonic stem/induced pluripotent stem cells) have been widely studied as a potential cell source for cell transplantation therapy of Parkinson's disease. However, some difficulties remain to be overcome. These include the need to prepare a large number of dopamine (DA) neurons for clinical use and to culture the cells for a long period to allow their functional maturation and the removal of undifferentiated cells. In this study, aggregates of DA neuron precursors were enclosed in alginate–Ca2+ microbeads, and the encapsulated aggregates were cultured for 25days to induce cell maturation. More than 60% of cells in the aggregates differentiated into tyrosine hydroxylase-positive DA neurons. The aggregates could release DA at the same level as aggregates maintained on culture dishes without encapsulation. In addition, by exposure to a citrate solution, the alginate–Ca2+ gel layer could be easily removed from aggregates without damaging the DA neurons. When the aggregates were transplanted into rat brain, viable cells were found in the graft at one week post-transplantation, with cells extending neurites into the host tissue. Cell aggregates encapsulated in alginate–Ca2+ beads successfully differentiated into mature DA neurons. The alginate–Ca2+ microbead is suitable for maintaining DA precursor aggregates for a long period to allow their functional maturation. •HiPS-derived precursor cells were encapsulated in alginate–Ca2+ beads.•Encapsulated cells were successfully differentiated into dopamine neurons.•DA neurons could be easily released from alginate–Ca2+ beads.•In a transplantation study, DA neurons integrated with the host brain.